IDENTIFICATION OF STUDENTS’ WORK IN RESOLVING THE PROBLEM OF POLYHEDRON - Samsul Faridz; Ani Ainun Masruroh; Eva Dwi Minarti (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
The research aims to identify students ' work in resolving the problem of polyhedron. This research used a qualitative descriptive method conducted at the state Junior High School in Batujajar. The instrument used in this research is a test of the problem that has been adjusted to the indicator of the polyhedron material of a) mention the elements of the cube, Cuboids, Prism, and Pyramid (ribs, field, side, diagonal field, diagonal space, field Diagonal); b) determines the surface area of the polyhedron c) The volume of polyhedron; d) solve the problem of polyhedron in daily life. Based on the research results of the 4 problems given are received percentage value in a row of 29.03%; 66.12%; 65.70%; 47.90% of the results showed that students are still struggling in determining the elements of polyhedron chamber and creating a mathematical model of the story related to everyday life.